Nutrient levels in browse and forb species eaten by cattle in the Paiaguás subregion of the Pantanal, Brazil - Pott, Edison Beno; Pott, Arnildo (Pesquisa Agropecuaria Brasileira, 2014)
Levels of Ca, Mg, P, K, Cu, Fe, Mn, Zn and crude protein (CP) were analysed in samples of leaves, leaves + twigs and fruits of non-grass native forage plants eaten by cattle in the subregion of Paiaguás, Corumbá, Mato Grosso do Sul, Brazil. Presence of high levels of Ca, Mg, P, K, Cu, Zn and/or CP were found in many species. In general, Fe and Mn levels in these plants were lower than in the grasses of the same subregion. Among the analysed plants, Bidens gardineri, Vernonia Scabra, Cordia glabrata, Chomella obtusa var. pubescens, Smilax sp., Helicteres cf. sacarolha, Myrcia sp., Erythroxylum subarosum, Cyperussp., Solanum viasrum (fruit), Byrsonima orbignyana, Tocoyena formosa, Casearia sp., Cecropia cf. pachystachya, Vitex cymosa and Fimbrystilis sp. were the species which stand out in number of nutrients with high levels. Based on the results and on degrees of acceptability by cattle and frequency of occurrence of the alternative forage plants, the following were elected as the most important ones: B. gardneri, Smilax sp., H. cf. sacarolha, C. glabrata, Costus sp., Cyperus sp., T. formosa, C cf. pachystachya, V. cymosa, Attalea phalerata, Stryphnodendron adstrigens and Eleocharis cf. fistulosa. It is concluded that there are non-conventional forage plants which complement or may complement cattle diet in the sandy Pantanal.
Keywords: minerals; crude protein; forage plants; shrubs; nutrition; calcium; phosphorus; magnesium; potassium; iron; copper; manganese; zinc; native pasture